The novel technique in simplifying the fabrication process and in improving the reflection coefficient of the linear polarized radial line slot array (LP-RLSA) antennas - Teddy Purnamirza (Kementerian Agama Republik Indonesia Direktorat Jenderal Pendidikan Islam Direktorat Pendidikan Tinggi Islam, 2012)
Hard,1/nr,c.1